Macroeconomic Determinants of External Debt in Selected SAARC Countries: A Panel Data Analysis - Danish, Muhammad Hassan; Jamshaid, Fouzia; Shahzadi, Samman (International Journal of Contemporary Economics and Administrative Sciences, 2021)
External debt is burning problem in almost all economically developing or underdeveloped countries because of current account and budget deficits, low saving and investment growth and negative balance of payment. The external borrowing is increasing drastically in South Asian Association for Regional Co-operation (SAARC) that largely relies on external borrowing for their public finance. So, this study aims to explore the factors which enhances or lower the external debt in four countries in four SAARC nations (Bangladesh, India, Pakistan and Srilanka) for the period of 1984-2019. Results of study explored that budget deficit, negative balance of payments, devaluation of currency and more corruption are major factors to increase external debt in these countries and are significantly related to external debt. So, it is recommended that exports should be encouraged, and governments of these countries need to provide export subsidies and introduce export bonus voucher schemes. Government needs to follow the cannons of taxations and need to give rebate on heavy taxes on import of manufacturing machinery and to encourage FDI.